1995
DOI: 10.1149/1.2048685
|View full text |Cite
|
Sign up to set email alerts
|

Polymer Electrolytes with Multiple Conductive Channels Prepared from NBR/SBR Latex Films Impregnated with Lithium Salt and Plasticizer

Abstract: Polymer electrolytes with high ionic conductivity (>10 -3 S/cm) and good tensile strength were prepared by swelling poly(acrylonitrile-co-butadiene) (NBR)/poly(styrene-ce-butadiene) (SBR)/LiC104 latex films with ~y-butyrolactone (~/-BL) or LiCIOJ~/-BL plasticizer. Before swelling, the LiCIQ phase is formed at the particle interface. After plasticization, two ion-conductive channels are present: the LiCIQ phase is present at the interface of the latex particles, and the NBR phase is formed from NBR latex partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…Here, we focused on the nitrile (CN) groups in the NBR. It is known that the polymers possessing CN groups such as NBR [16][17][18] and PAN 19,20) can dissolve many types of alkali metal (Li) salts and show good conductivities. Considering the fundamental properties of the CN group in the electrolyte materials, it has the strong electron withdrawing nature and can easily interact with Lewis acids such as alkali metal cations.…”
Section: Resultsmentioning
confidence: 99%
“…Here, we focused on the nitrile (CN) groups in the NBR. It is known that the polymers possessing CN groups such as NBR [16][17][18] and PAN 19,20) can dissolve many types of alkali metal (Li) salts and show good conductivities. Considering the fundamental properties of the CN group in the electrolyte materials, it has the strong electron withdrawing nature and can easily interact with Lewis acids such as alkali metal cations.…”
Section: Resultsmentioning
confidence: 99%
“…Table 1 summarises the main polymer blend SPEs and their ionic conductivity. The blend type SPEs hitherto documented divide broadly into three categories: simple blend type [5][6][7], polymer electrolyte type [8][9][10][11], and elastomer type [12][13][14]. The simple blend SPEs, the type most often studied, are basically blends of PEO-metal salt complexes with other polymers.…”
Section: Blend Type Spes and Their Characteristicsmentioning
confidence: 99%
“…An example is gel type electrolyte formed by impregnating an electrolyte fluid (such as LiClO 4 solution in g-butyrolactone) in an elastomer blend consisting of NBR and SBR. The electrolyte fluid preferentially impregnates the NBR phase of the NBR/ SBR blend, which forms a co-continuous phase-separation structure, the intention being to achieve effective ion transport via the network structure [12]. Another report [13] describes a single ion conductive SPE blend in which PEO oligomer containing terminal benzenesulphonate groups has been mixed with natural rubber (NR).…”
Section: Blend Type Spes and Their Characteristicsmentioning
confidence: 99%
“…The present study focussed on the use of acrylonitrile-buta diene rubber (NBR) as an elastomer that has both a relatively low glass transition temperature (T g ) and a high polarity. A number of studies of the application of NBR to SPE have already been reported [11,12], almost all relating to hybrid systems utilising liquid electrolyte (gels); none has sought to develop a "dry" SPE exploiting the intrinsic properties of NBR.…”
Section: Introductionmentioning
confidence: 99%